About a variant of the finding of the solution equation by Ginsburg-Landow - Nazarova, K.Zh. (Bulletin of the Karaganda University. Mathematics Series, 2015)
In article numerical analysis nonlinear of two - point boundary value problem for the equation of Ginsburg - Landow is given by modified parametrization’s method. Isolated solutions of the problems in question are received. The problem describes the stationary positions of the superconducting endless plate of final depth, which are placed in the magnetic field.